101 favorite play therapy techniques. - Kaduson, Heidi; Schaefer, Charles E. (Child therapy series., 2010)
This book is an amazing resource for play therapy techniques. The contributors come from a diverse group including child-centered, cognitive-behavioral, gestalt, Jungian, psychodynamic, and prescriptive play therapy.